A motivational approach to perfectionism and striving for excellence: Development of a new continuum-based scale for post-secondary students - Lasalle, Marie; Hess, Ursula (Frontiers in Psychology, 2022)
Perfectionism has been the object of many disputes. One such debate pertains to the nature of perfectionistic strivings. Whereas perfectionistic concerns (PC) have been shown to correlate with negative outcomes, perfectionistic strivings (PS) have been associated with mixed outcomes. This view of perfectionism assumes a motivational perspective; however, commonly used questionnaires assess motivation only implicitly. To create a more explicit measure of motivation as regards perfectionism, we aimed to assess perfectionism in post-secondary education based on Deci and Ryan’s self-determination continuum. We posit that introjected motivation represents the variance common to both dimensions of perfectionism. External motivation is considered to be specific to PC and identified motivation to PS. Amotivation represents a lack of striving. Intrinsic motivation, lacking perfectionism’s pressure, is conceptualized to be a self-determined form of striving for excellence. We further posited that this continuum is implicitly underlain by a continuum of self-definition as defined by Blatt. The resulting questionnaire showed an adequate structure with ESEM, followed a simplex structure, and had adequate reliabilities (Study 1a/Study 2). It also showed adequate convergent validity (Study 1b/Study 2). Finally, the questionnaire proved to be invariant over a six week period (Study 2). Results suggest that the degree of active goal pursuit, in addition to standards setting, could be a distinguishing characteristic between dimensions of perfectionism as well as striving for excellence.